Aplicação de carvacrol e 1,8-cineol na inibição de bactérias contaminantes de hortaliças minimamente processadas em inóculo misto - Oliveira, Kataryne árabe Rima de (2014)
The demand for fresh foods, with lower calories, high nutritional values and easily prepared has been increased the consumption of minimally processed vegetables. However, because the intense handling these products has been considered a potential problem to the microbiological safety, related mainly to the presence of psychrotrophic pathogenic and spoilage bacteria. The sanitization is considered a critical processing step for minimally processed vegetables, although some of the synthetic sanitizers allowed for the use in vegetables are cited as responsible for undesirable effects to consumers. In this context, as alternative to the synthetic sanitizers arise the essential oils, whose antimicrobial action mechanism is attributed, many times, to their majority compounds. Regarding these aspects, this study aimed to evaluate the potential application of carvacrol and 1,8-cineole against some strains of minimally processed vegetables contaminant bacteria (Listeria monocytogenes ATCC 7644, Aeromonas hydrophila INCQS 7966 and Pseudomonas fluorescens ATCC 11253), in mixed culture, by determining the values of Minimum Inhibitory Concentration (MIC), the index of Fractional Inhibitory Concentration (FIC), as well as by assessing the efficacy of the application of these compounds in inhibiting the growth and survival of the mixed bacterial inoculum in vegetable broth and in leafy vegetables. Moreover, it was performed the assessment of possible damage caused by the tested compounds in the morphology of the bacterial cells by the analysis of confocal microscopy and scanning electronic microscopy. MIC values of carvacrol and 1,8-cineole ranged from 1.25 e 40μL/mL, respectively. The FIC index against the mixed bacterial inoculum was 0.25, suggesting a synergic interaction between the tested compounds. The application of the compounds alone or combined in sub-inhibitory concentrations in vegetable broth caused a significant decrease (p <0.05) in counts (CFU/mL) of the tested bacteria over 24 h. The exposure of vegetables to the compounds for only 5 min also caused a significant reduction (p < 0.05) in counts of the tested bacteria. The observations of bacterial cell morphology suggest that the compounds carvacrol and 1,8-cineole alone or combined in sub-inhibitory concentrations, cause damage to the cell viability, and change the permeability of the cytoplasmic membrane and the cell surface, with the appearance of roughness appearance and like-vesicles structures. These results show that carvacrol and 1,8-cineole possess strong inhibitory effect of the growth and survival of bacteria associated with minimally processed vegetables when tested in mixed culture. Still, these data confirm that constituents of essential oils, with different molecular structures, when applied in combination can replace traditional synthetic sanitizing used in minimally processed vegetables allowing reaching the balance between the demand for microbiological safety and sensory acceptability of these products.